New species and records of Paraphloeostiba Steel, 1960 from China and Laos, and descriptions of four new species of related genera (Coleoptera: Staphylinidae: Omaliinae: Omaliini) - Shavrin, Alexey V. (Zootaxa, 2020)
New taxonomic and faunistic data for eight species of Paraphloeostiba Steel, 1960 (Omaliini) from China and Laos are provided. Three new species are described and illustrated: P. ampliata sp.n. (China: Yunnan), P. brancuccii sp.n. (Laos), and P. cooteri sp.n. (China: Zhejiang). A new synonymy is established: P. formosana Shavrin & Smetana, 2016 = P. amooraphila Shavrin, 2017 syn.n. Paraphloeostiba opacicollis Steel, 1960 is redescribed, illustrated, and recorded from Laos for the first time. A key to the species of Paraphloeostiba of China and Laos is presented. Previous records of P. apicalis (Cameron, 1925) from China are doubtful; additional material from Indonesia and the Philippines is reported. Paraphloeostiba sulcicollis (Fauvel, 1904) is recorded from China for the first time. New records of Paraphloeostiba are reported: P. apicalis from Mindanao (Philippines), P. formosana Shavrin & Smetana, 2016 from mainland China and Vietnam, P. gayndahensis (MacLeay, 1873) from Yunnan, and P. sonani (Bernhauer, 1943) from Myanmar. In addition, four new species of Omaliini are described and illustrated: Nipponophloeostiba longilobata sp.n., Omalium khmericum sp.n., and Phloeostiba assingi sp.n. from northern Laos, and Phloeonomus (Phloeonomus) rougemonti sp.n. from China (Yunnan).